2021
DOI: 10.1183/13993003.00224-2021
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in COVID-19: one size does not fit all

Abstract: This manuscript has recently been accepted for publication in the European Respiratory Journal. It is published here in its accepted form prior to copyediting and typesetting by our production team. After these production processes are complete and the authors have approved the resulting proofs, the article will move to the latest issue of the ERJ online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…It just emphasises that the decision to use corticosteroids needs to be individually tailored, first and foremost according to age, but also with regards to comorbidities and other factors. [7] Our analysis has limitations: First, this is a secondary analysis of a prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…It just emphasises that the decision to use corticosteroids needs to be individually tailored, first and foremost according to age, but also with regards to comorbidities and other factors. [7] Our analysis has limitations: First, this is a secondary analysis of a prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a large proportion of patients received concomitant corticosteroids (up to 60% overall; Table S1 in the Supporting Information) in these studies, and possibly in some instances in higher doses as life-saving treatment. 81 In our secondary analysis, a reduction in mortality was observed irrespective of the use of systemic corticosteroids; however, combination therapy had a more pronounced effect on mortality (RR 0.57 in the corticosteroids group vs. 0.70 in the no-corticosteroids group). The data from observational studies, despite their significant heterogeneity, overall support the observation in RCTs for a beneficial effect of tocilizumab on mortality, which may be more prominent in addition to systemic corticosteroids that anyway represent the cornerstone of treatment of patients with COVID-19 and respiratory failure.…”
Section: Discussionmentioning
confidence: 60%
“…These studies are characterized by significant heterogeneity regarding participants' characteristics, study protocols, drug dosage and route of administration, standard of care regimens and, most importantly, a plausible selection bias in the decision for administration of tocilizumab. Notably, a large proportion of patients received concomitant corticosteroids (up to 60% overall; Table S1 in the Supporting Information) in these studies, and possibly in some instances in higher doses as life‐saving treatment 81 . In our secondary analysis, a reduction in mortality was observed irrespective of the use of systemic corticosteroids; however, combination therapy had a more pronounced effect on mortality (RR 0.57 in the corticosteroids group vs. 0.70 in the no‐corticosteroids group).…”
Section: Discussionmentioning
confidence: 97%
“…Dexamethasone is usually given to hospitalized COVID-19 patients requiring oxygen therapy. In a recent report, it was shown that in patients hospitalized with COVID-19, the use of Dexamethasone resulted in lower 28-day mortality among those who were receiving either invasive mechanical ventilation or oxygen alone at random, but not among those receiving no respiratory support [205][206][207].…”
Section: Corticosteroid Compoundsmentioning
confidence: 99%